2001
DOI: 10.1262/jrd.47.139
|View full text |Cite
|
Sign up to set email alerts
|

Determination by Real-Time RT-PCR of Imprinted Expression of the Insulin-Like Growth Factor II (Igf2) Gene in Mouse Uniparental Fetuses.

Abstract: Abstract. Uniparental mouse embryos are generally used in the study of imprinting mechanisms as models to determine parental expression of imprinted genes. In this study, we used the real-time RT-PCR method to carry out a quantitative analysis of the expression of the insulin-like growth factor II (Igf2) gene, which is imprinted and expressed solely from the paternal allele, in androgenetic and parthenogenetic fetuses at day 9.5 of gestation. The mean expression, relative to that of control biparental fetuses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
1
1
Order By: Relevance
“…We previously reported that the expression of the paternally expressed gene Igf2 in androgenetic fetuses was slightly accelerated to 1.5 times the expected value (31). Surprisingly, however, in the present study the expressions of the H19 and Igf2r genes in parthenogenetic fetuses were more than two and six times the expected values, respectively, and the expressions were far different from that of the Igf2 gene in androgenetic fetuses.…”
Section: Fig 3 Analysis Of Allele-specific Expression Of the H19 Andcontrasting
confidence: 89%
“…We previously reported that the expression of the paternally expressed gene Igf2 in androgenetic fetuses was slightly accelerated to 1.5 times the expected value (31). Surprisingly, however, in the present study the expressions of the H19 and Igf2r genes in parthenogenetic fetuses were more than two and six times the expected values, respectively, and the expressions were far different from that of the Igf2 gene in androgenetic fetuses.…”
Section: Fig 3 Analysis Of Allele-specific Expression Of the H19 Andcontrasting
confidence: 89%
“…DISCUSSION We reported previously that expressions of mouse paternally expressed imprinted genes Peg1/Mest (16), Igf2 (14), Peg3 (18), and Snrpn (29) are not properly detected by RT-PCR in mouse parthenogenetic fetuses at day 9.5 of gestation (30). Further analysis by real-time quantitative RT-PCR confirmed parental specific expression of the Igf2 gene in both the parthenogenetic and androgenetic fetuses (31). These previously published observations show that parental expression of imprinted genes is generally maintained in uniparental fetuses.…”
Section: Resultssupporting
confidence: 68%
“…Many imprinted genes, such as Igf2, Igf2r, Peg1/Mest, Peg3, and H19, maintain their parental specific expression in uniparental embryos (13,16,18,31,35), that is, in parthenogenetic/ gynogenetic and androgenetic embryos. However, the present results show that this is not the case for the U2afbp-rs.…”
Section: Figmentioning
confidence: 99%